Produtividade da soja sobre palhada de forrageiras semeadas em diferentes épocas e alterações químicas no solo - Costa, Nídia Raquel [UNESP]; Andreotti, Marcelo [UNESP]; De Araújo Ulian, Nelson [UNESP]; Costa, Bruno Sorati [UNESP]; Pariz, Cristiano Magalhães [UNESP]; Cavasano, Francielli Aparecida [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Revista Brasileira de Ciencias Agrarias, 2015)
This study aimed to evaluate the dry mass yield (PMS) of forages due to sowing times, with the crop components and grain yield (PG) of soybean cultivated in succession to forages under irrigated conditions and alterations in the soil chemical properties. The experimental design was a randomized block with four repetitions in a factorial scheme 3 × 3, being: 3 species of forage plants: forage sorghum (Sorghum bicolor (L.) Moench), pearl millet (Pennisetum glaucum (L.) R. Br) and Xaraés grass (Urochloa brizantha Xaraés) and three sowing times (14/09/09 (E1), 29/09/09 (E2) and 14/10/09 (E3) managed at 45 days after emergence. For the second growing season, the sowing dates were: 10/09/10 (E1), 27/09/10 (E2) and 20/10/10 (E3). The highest PMS were obtained for pearl millet and sorghum. Regardless of the forage species, the best sowing time was E3. The higher PG soybeans were obtained under forage sorghum straw and Xaraés grass, being the best options in the soybean crop predecessor since sown in late September or middle of October (E2 and E3). In the E3 there was increase in the values of H+Al and CTC. Sowing in E3 of Xaraés grass and pearl millet propitiated lower contents of OM, in the first cultivation.
Soybean yield on straw forages sown at different times and changes in chemical soil
Keywords: Glycine max; No tilage system; Pennisetum glaucum; Sorghum bicolor; Urochloa brizantha